When Lightning Comes In A Jar - Patricia Polacco (China Philomel Books, 2002)
It's family reunion time! Trisha and her cousins can hardly wait to see one another again. They can't decide what they like best: the great feast (with zillions of meatloafs and gazillions of Jell-O salads), the softball game, the storytelling . . . the yearly rituals go on and on. But this year, Gramma has a new surprise in store: She promises to teach the grandchildren to catch lightning in a jar. Lightning in a jar! Trisha can't wait to find out what she means. It's a secret she will pass down to her own grandchildren one day, along with the family stories handed down with love
Keywords: Read Aloud -- Read Aloud